The Law of Demand–The Roles of Gregory King and Charles Davenant - Evans, G. Heberton (Quarterly Journal of Economics, 1967)
I. A sentence in King's working-journal, 483. — II. Some previous statements about King's law, 485. — III. Davenant's role, 488. — IV. Early variations of the demand schedule, 491. — V. Conclusion, 492.